2014
DOI: 10.22146/jsv.3801
|View full text |Cite
|
Sign up to set email alerts
|

A Life Table of Spodoptera litura Fabr. with Different Artificial Diets

Abstract: Sustainable insect supply is a routine activity in research of pest control, experimental insecticide bioassay, entomophatogen, parasitoid, and nature of competitor. Armyworm (Spodoptera litura Fabr.) is one of the alternative test insect. A mass rearing method is required to provide high demands of S. litura. A life table of insect is regularly used to study several biological parameters including the net reproduction rate of population (Ro), the mean length of life period in one generation (T), reproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Carbohydrate content plays more of a role as a source of nutrition. Carbohydrate content at a certain amount can produce more optimal growth [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrate content plays more of a role as a source of nutrition. Carbohydrate content at a certain amount can produce more optimal growth [21].…”
Section: Discussionmentioning
confidence: 99%
“…This is related to the protein content of the feed plants. A higher protein content in the feed resulted in a shorter average life span of one generation and higher reproductive potential [21]. Larvae utilize the protein content to form body tissues that transcend the instar stage during development…”
Section: Discussionmentioning
confidence: 99%
“…This species has been widely reported for its attacks on various agricultural commodities such as chili, cabbage, rice, corn, tomatoes, tobacco, eggplant, beans, soybeans, and peanuts which can cause yield losses of up to 80% [14,15,16]. Several studies have reported life tables of S. litura which contain basic data on the population dynamics of various host plants [17,18,19]. The life table is useful for determining the weakest moment of a pest's life cycle so that it can increase the potential for successful pest control.…”
Section: Spodoptera Lituramentioning
confidence: 99%
“…Hama ini juga dilaporkan memiliki potensi reproduksi yang tinggi karena setiap imago betina mampu menghasilkan hingga 1.500 butir telur (Capinera 2001). Menurut Lestari et al (2013), fekunditas imago betina S. litura yang diberi pakan buatan resep Waldbauer et al (1984) sebanyak 2.133,2 telur. Bahkan sampai 5.293,8 telur ketika diberi pakan dengan resep Singh & Moore (1985).…”
Section: Pendahuluanunclassified